2019
DOI: 10.1002/esp.4620
|View full text |Cite
|
Sign up to set email alerts
|

Sidewall erosion: Insights from in situ‐produced 10Be concentrations measured on supraglacial clasts (Mont Blanc massif, France)

Abstract: Sidewall erosion because of rockfalls is one of the most efficient erosional processes in the highest parts of mountain ranges; it is therefore important to quantify sidewall erosion to understand the long‐term evolution of mountainous topography. In this study, we analyse how the 10Be concentration of supraglacial debris can be used to quantify sidewall erosion in a glaciated catchment. We first analyse, in a glaciated catchment, the cascade of processes that move a rock from a rockwall to a supraglacial loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 75 publications
(173 reference statements)
2
20
0
Order By: Relevance
“…inherited 10 Be concentration produced during the last glacial cycle) was an overestimation. This higher rockfall frequency is also confirmed by 10 Be measurements in supra-glacial clasts collected in Bossons and Argentière glacier areas (MBM), revealing significant rockfall erosion in glacier sidewalls (Sarr et al, 2019). We thus consider that the inherited 10 Be content in our collected samples is non-significant for exposure age computation.…”
Section: Sample Processingsupporting
confidence: 79%
“…inherited 10 Be concentration produced during the last glacial cycle) was an overestimation. This higher rockfall frequency is also confirmed by 10 Be measurements in supra-glacial clasts collected in Bossons and Argentière glacier areas (MBM), revealing significant rockfall erosion in glacier sidewalls (Sarr et al, 2019). We thus consider that the inherited 10 Be content in our collected samples is non-significant for exposure age computation.…”
Section: Sample Processingsupporting
confidence: 79%
“…The benefit of this approach is that (1) the estimated erosion rates represent values that are spatially and temporally averaged across relatively large headwall areas; (2) the source areas of the debris can be reconstructed, e.g., from remote‐sensing images; and (3) the sampling procedure is relatively straightforward. However, despite a promising initial application (Ward & Anderson, 2011), this approach has rarely been employed (e.g., Guillon et al, 2015; Sarr et al, 2019), and its applicability in different settings remains to be tested. Here we present headwall erosion rates derived from 10 Be concentrations in the ablation‐dominated medial moraine of the Chhota Shigri Glacier, Indian Himalaya.…”
Section: Introductionmentioning
confidence: 99%
“…(2017; http://calibration.ice-d.org/) and a 10 Be half‐life of 1.387 Ma (Chmeleff 2010; Korschinek 2010). Ward and Anderson (2011) and others have demonstrated that muonic production of 10 Be within amalgamated supraglacial debris sourced from the rockwall is negligible, and for the process timescales of rockwall slope erosion can be omitted from our calculation scheme (Akçar et al., 2014; Braucher et al., 2003; Sarr et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This approach to quantifying rockwall slope erosion accounts only for the spallogenic component of incoming cosmic rays and assumes a negligible loss of 10 Be due to radioactive decay, and steady state erosion and 10 Be production over time (von Blanckenburg, 2005). Further details of this methodology and its assumptions are provided by Supplementary Item 1 and in Ward and Anderson (2011) and Sarr et al (2019).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation